Diaper dermatitis prevalence and severity: Global perspective on the impact of caregiver behavior. Issue 1 (2nd December 2019) - Carr, Andrew N.; DeWitt, Thomas; Cork, Michael J.; Eichenfield, Lawrence F.; Fölster‐Holst, Regina; Hohl, Daniel; Lane, Alfred T.; Paller, Amy; Pickering, Larry; Taieb, Alain; Cui, Tao Y.; Xu, Zi G.; et al.
Abstract: Objectives: To compare prevalence and severity of diaper dermatitis (DD) in infants and toddlers (babies) across three countries (China, USA, and Germany), including diapered skin measures and caregiver practices. Methods: A cross‐sectional study of 1791 babies (~600 from each country) was recruited at each clinical site. Based on regional toilet‐training habits, exclusively diaper‐wearing infants were recruited between ages 2‐8 months in China and 2‐18 months in the USA and Germany. DD was measured, as well as skin pH, transepidermal water loss (TEWL), and relative humidity (RH) in the diapered region. Caregiver habits were collected via a questionnaire and included information on hygienic practices. Results: Diaper dermatitis was highest in the perianal area, followed by the intertriginous, genital, and buttock regions. In general, DD was significantly lower in babies in China, highest in Germany, and intermediate in the USA. This rank ordering of DD by geography was also observed in baby age 2‐8 months. The lower DD observed in China was associated with lower skin pH and TEWL on diapered skin and decreased RH in the diaper. Chinese caregivers had the highest rate of prophylactic topical product usage, the most robust cleaning of the diapered area, lack of cleansing after urine‐only diaper changes, and Chinese infants spent the least time in an overnight diaper. Conclusions: These data suggest caregiver behaviors including prophylactic use of topical products, thorough cleaning after stooling and reduced time in an overnight diaper are associated with less DD, lower superficial skin pH, and enhanced skin barrier.